Why does a creative city need its local music? A study of the contemporary Wroclaw jazz scene - Kopaniecki, Jakub (Interdisciplinary Studies in Musicology, 2021)
The aim of the article is to look at serious musical leisure activities in selected places in Wroclaw, in order to explain their significant contribution to making the capital of lower Silesia a creative city. Taking the perspective of research on music scenes and leisure studies, the author tries to demonstrate that the music scene in Wroclaw, although it didn’t develop its original sound, functions in a very effective way, providing a space for personal development, shaping the identity of individuals and the entire city. The discussed places not only serve as a physical space for a performance but primarily are communities based on internal and external cooperation. They are real “meeting places,” as the promotional slogan of Wroclaw says, for audiences and performers, amateurs, and professionals alike. The article is based on research on the Wroclaw music scene conducted since 2019. live performances that took place before the COvID-19 pandemic and between subsequent lockdowns were taken into account.